The Mediating Role of Sustainable Value Creation in the Relationship Between Information Technology and Competitive Advantage - Ahmad Badawi; Wiwik Utami; Bambang Marsoem; Augustina Kurniasih (Australasian Accounting, Business and Finance Journal, 2024)
This study aims to analyze and determine the magnitude of the influence of information technology capabilities, leadership commitment, competitive advantage and sustainable value creation. This study uses descriptive and causal-explanatory methods with a quantitative approach. The sampling method used is the probability sampling approach (the census). Data analysis used is the Structural Equation Modeling (SEM) approach using primary data. The results of the study state that IT Capability has a significant positive effect on Sustainability Value Creation (SVC) and Corporate Competitive Advantage (CCA). The Top Management Commitment variable positively and significantly affects Sustainability Value Creation but does not affect CCA. The SVC variable influences CCA. The results of the Indirect Effect test state that IT Capability influences CCA through SVC. Meanwhile, Top Management Commitment influences CCA through SVC. Additional variables may have other moderating and mediating effects on the mediating role of sustainable value creation. This research contributes to knowledge development (basic research) and applicative problem solving (applied research) by Islamic banking in Indonesia. The results of this study can be a premise for subsequent researchers and can add to the limitations of the literature. This research focused on the research locus, namely Islamic banking throughout Indonesia. It is confirmed that research topics with variables used in this research have never been studied at the locus of Islamic banking before.
Keywords: IT capability; sustainability value creation; corporate competitive advantage; management commitment